ANALISIS MIKROPLASTIK DI INSANG DAN SALURAN PENCERNAAN IKAN KARANG DI TIGA PULAU KECIL DAN TERLUAR PAPUA, INDONESIA: KAJIAN AWAL - Yona, Defri; Maharani, Mela Dita; Cordova, M. Reza; Elvania, Yuyun; Dharmawan, I Wayan Eka (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2020)
Microplastics have been found widely in marine environments, including the remote areas far from human activities, and can be ingested by fish. This study aimed to investigate microplastics from 12 coral reef fishes of three small outer islands of Papua (Liki, Befondi, and Miossu) and to analyze the difference of microplastic concentrations in gill and gastrointestinal tract. Fish samples were obtained using a hand line and dissected to separate the gills and gastrointestinal tracts. The destruction method using H2O2 30 % was conducted to separate organic matter, and the microscope was used to identify microplastic types. Fibers were found in all fish species in the range of 1.60-28.30 particle/g dry weight. Microplastics in fishes from Liki Island were higher compared to the ones from Befondi and Miossu Islands. The results of this study observed that there is no relationship between fish size and microplastic concentration since the size of fishes from Liki Island were smaller than the ones from the two islands. Most fishes were observed to contain fiber in both the gill and gastrointestinal tract, with the dominant size of microplastic was > 1000 µm. This study found that microplastics in the gills were higher than in the gastrointestinal tracts, and it is related to the difference in the organ functionality and the process of microplastic entering the organs from the surrounding water.